2017
DOI: 10.1038/s41598-017-16930-0
|View full text |Cite
|
Sign up to set email alerts
|

MALE STERILE6021 (MS6021) is required for the development of anther cuticle and pollen exine in maize

Abstract: The anther cuticle and pollen wall function as physical barriers that protect genetic material from various environmental stresses. The anther cuticle is composed of wax and cutin, the pollen wall includes exine and intine, and the components of the outer exine are collectively called sporopollenin. Other than cuticle wax, cutin and sporopollenin are biopolymers compounds. The precise constituents and developmental mechanism of these biopolymeric are poorly understood. Here, we reported a complete male sterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…() and Tian et al . (), have shown the importance of exine development for pollen viability. Among these, Lou et al .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…() and Tian et al . (), have shown the importance of exine development for pollen viability. Among these, Lou et al .…”
Section: Resultsmentioning
confidence: 98%
“…Numerous studies, such as Quilichini et al (2015), Choi et al (2011), Chen et al (2011 and Tian et al (2017), have shown the importance of exine development for pollen viability. Among these, Lou et al (2014) found that knockout of AtTEK, which is involved in nexine formation, resulted in the absence of nexine, no intine and male-sterility in Arabidopsis thaliana.…”
Section: Phenotype Analysis Of Ms5amentioning
confidence: 99%
“…We hypothesize that delayed PCD of the inner four anther layers in ms305, including tapetum cells, leads to the degradation of pollen grains, and this should be responsible for its complete male sterility. Lipids play an important role in regulating plant anther development, a large number of studies have reported the role of fatty acids and their derivatives in regulating anther fertility [15,29,42]. For example, anther cuticle, including cutin and wax, can protect plant anthers from hydration [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, anther cuticle, including cutin and wax, can protect plant anthers from hydration [26]. In maize, MS45, MS26, MS30, MS33, IPE1, and APV1 are reported to participate in the aliphatic metabolic pathways, which are required for anther cuticle development [19,26,29,39,43]. The abortion characteristics of MS30, MS33, IPE1, and APV1 in maize were described, such as the swollen microspore and the decreased vacuole of APV1 at the vacuolated stage [19], severe degradation of the tapetum in IPE1 [20] and an obvious abortion of MS30 first appeared after the vacuolated stage [15], these were, however, different from ms305.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation